PROGRAM RUMAH SRIKANDI SEBAGAI PROGRAM CSR PT. SARIHUSADA (Studi Kasus: Pemberdayaan Masyarakat Di Desa Logede Kecamatan Karangnongko Kabupaten Klaten ) - Prihatin Saraswati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2021)
This research aims to discuss the implementation of the CSR program PT. Sarihusada Generasi Mahardika through srikandi house program as a community empowerment program in Logede village of Karangnongko District Klaten Regency. This type of qualitative research is described to obtain data on the performance of CSR programs through Sri Kandi's home activities and their benefits for logede villagers. Data collection is done by interview methods and documentation to obtain data. Then the data is analyzed using miles and Huberman model data analysis that followed the stage of data reduction, data display, and conclusions. The study results showed that the community empowerment program through Rumah Srikandi has been following the stage of community empowerment, namely the awareness stage to the location of independence and beneficial for the community. This can be seen from the formation of FMDL as a forum for the realization of programs, namely Maternal and Toddler Health, Yandu cadre training that aims to overcome malnutrition, and microeconomic programs, namely waste bank management, organic fertilizer nutrition gardens, and tempeh production that until now has reached the stage of independence.